Randomized trial of cognitive training and brain stimulation in non‐demented older adults - Daria Antonenko; Friederike Thams; Ulrike Grittner; Jessica Uhrich; Franka Glöckner; Shu‐Chen Li; Agnes Flöel (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Given rapid global population aging, developing interventions against age‐associated cognitive decline is an important medical and societal goal. We evaluated a cognitive training protocol combined with transcranial direct current stimulation (tDCS) on trained and non‐trained functions in non‐demented older adults. Methods Fifty‐six older adults (65–80 years) were randomly assigned to one of two interventional groups, using age and baseline performance as strata. Both groups performed a nine‐session cognitive training over 3 weeks with either concurrent anodal tDCS (atDCS, 1 mA, 20 minutes) over the left dorsolateral prefrontal cortex (target intervention) or sham stimulation (control intervention). Primary outcome was performance on the trained letter updating task immediately after training. Secondary outcomes included performance on other executive and memory (near and far transfer) tasks. All tasks were administered at baseline, post‐intervention, and at 1‐ and 7‐month follow‐up assessments. Prespecified analyses to investigate treatment effects were conducted using mixed‐model analyses. Results No between‐group differences emerged in the trained letter updating and Markov decision‐making tasks at post‐intervention and at follow‐up timepoints. Secondary analyses revealed group differences in one near‐transfer task: Superior n‐back task performance was observed in the tDCS group at post‐intervention and at follow‐up. No such effects were observed for the other transfer tasks. Improvements in working memory were associated with individually induced electric field strengths. Discussion Cognitive training with atDCS did not lead to superior improvement in trained task performance compared to cognitive training with sham stimulation. Thus, our results do not support the immediate benefit of tDCS‐assisted multi‐session cognitive training on the trained function. As the intervention enhanced performance in a near‐transfer working memory task, we provide exploratory evidence for effects on non‐trained working memory functions in non‐demented older adults that persist over a period of 1 month.